Expert System for Safety Recommendations of Active Ingredients Combinations Based on Skin Conditions Using a Rule-Based System - Fitra Ramadhan Lubis; Wilda Rina Hasibuan (Takaza Innovatix Labs Ltd., 2026)
The growth of skincare products increases the need for easily accessible information regarding the safety of active ingredient combinations based on skin conditions. This study aims to develop an expert system that provides recommendations for the safety of active ingredient combinations based on the user's skin condition. The study used a system development method with a Rule-Based System approach and the Forward Chaining inference method. The study did not use conventional human populations and samples, but rather used peer-reviewed literature data from 2022–2025 and expert validation. The research instrument consisted of 25 condition rules covering six active ingredients, five skin conditions, and 15 unique active ingredient pairs. Data analysis was carried out through content analysis and expert validation using a four-level scale. The results showed that the system was able to generate recommendations in three categories: Recommended, Caution, and Not Recommended. Black Box testing showed that the authentication, knowledge base management, consultation, combination analysis, and prediction history functions ran as needed. In conclusion, the developed system can be used as an initial consultation medium to provide structured and easily accessible information on active ingredient safety